Quality Management Practices and Performance: Where are we, and where we are headed? The Perspective of Public Healthcare Institutions in Kenya - Nyangulika Jumapili, Dorcas; A. Muathe, Stephen Makau (European Scientific Journal, ESJ, 2025)
The global economy’s transformations have prompted public healthcare institutions in Kenya to adopt strategies to expand their markets, improve customer satisfaction, and enhance operational efficiency globally. The county government of Tharaka Nithi and the Kenyan national government have implemented initiatives to enhance public healthcare facilities, but their performance remains below the required standards. According to The World Health Organization reports Kenya’s public healthcare institutions provided 75% unsatisfactory services to customers, while their services remained at 6.6% from 2017 to 2020. Therefore, the current study investigated the effect of quality management practices on the performance of public healthcare institutions in Tharaka Nithi County, Kenya. Specifically, the study examined the effect of customer focus and continuous improvement on the performance of public healthcare institutions in Tharaka Nithi County, Kenya. The study used Scorecard, Six Sigma theories as well as the upper echelon theory. The study embraced descriptive research design. The target population was eight hundred and eighty-three employees of public healthcare institutions in Tharaka Nithi County, Kenya. Stratified random sampling techniques were used as a sampling technique to select 275 respondents that were determined scientifically through a formula. Primary data was collected using a structured self-administered questionnaire. A pilot test of twenty-eight respondents was conducted. The study instrument’s reliability and validity were evaluated using Cronbach’s alpha coefficient, with a threshold of 0.7 or higher. The collected data was analyzed using descriptive and inferential statistics, which were presented in the form of tables, charts, and graphs. The findings were that customer focus (p<0.05) continuous improvement (p<0.05) and top management commitment (p<0.05) all had a significant effect on the performance of public healthcare institutions in Tharaka Nithi County, Kenya. The study concluded that total quality management practices are significant enablers of the organizational performance of an institution. The study recommended that employees working with public healthcare institutions in Tharaka Nithi County should be motivated to address customer inquiries promptly to improve the level of efficiency and effectiveness. The operational managers and all other heads of the functional areas in the public healthcare institutions in Tharaka Nithi County design their processes effectively for effective decision-making. Employees should be encouraged to use errors reported as the basis for further improvement in processes.